Investigating design changes in Malaysian building projects - Yap, Jeffrey Boon Hui; Skitmore, Martin (Taylor & Francis, 2018)
The complexity and uncertainties associated with construction projects mean that contracts invariably provide sufficient flexibility for changes in design as the work proceeds. However, the concomitant effects of this arrangement often cause time and cost control to be adversely affected–resulting in schedule delays and cost overruns. In seeking an improved understanding, this study aimed to identify the specific causes of design changes and their implications –cost performance of Malaysia-based building projects. A total of 39 causes were first identified through a comprehensive literature review and, in conjunction with 12 semi-structured interviews with experienced construction industry practitioners, then categorised into those originating from clients, consultants, contractors, site and external sources. A questionnaire survey of 338 clients, consultants and contractors was then analysed to infer and rank the identified causes and their overall effect. The research reveals that building projects in Malaysia encounter time–cost overruns of 5–20% due to design changes. Lack of coordination among various professional consultants, change of requirements/specification, addition/omission of scope, erroneous/discrepancies in design documents and unforeseen ground conditions are the five most significant causes. The analysis also reveals considerable heterogeneity of perceptions between the respondent groups of the most significant causes of design changes, attributed to the adversarial culture within the industry.